Determination of bisphenol A in red wine using a double vortex–ultrasound‐assisted microextraction assay: Role of the interfacial properties. (19th February 2019) - Cinelli, Giuseppe; Cuomo, Francesca; Ambrosone, Luigi; Venditti, Francesco; Lopez, Francesco
Abstract: Bisphenol A (BPA) is a synthetic compound broadly used in medical devices as well as in packaging of food and drinks. Recently, BPA toxicity has become of concern to environmental public health. Red wine that is susceptible to BPA contamination is an alcoholic beverage made from yeast fermentation of grapes in the presence of grape skins so as to extract phenolic compounds. The aim of this study was to validate an efficient, low cost, and time‐saving method for BPA determination in red‐wine beverage. To this end, a rapid and simple microextraction method is here proposed consisting in liquid–liquid separation assisted by a vortex–ultrasound–vortex procedure combined with gas chromatographic analysis (GC‐Fid or GC‐IT/MS). By means of a comparative study between real red‐wine matrix and synthetic hydroalcoholic solutions, different parameters related to the microextraction steps were investigated. The minimal amount of extraction solvent for a given volume of sample was calculated for both the systems. It was demonstrated that for red‐wine matrix, the extent of phase separation is strongly affected by some wine constituents and that separation can be tuned by varying the amount of the extraction solvent. This double vortex–ultrasound‐assisted method achieved high recovery of BPA and enrichment factor compared with other microextraction methods.